A study on the factors that influence absenteeism among the employees of Syarikat Air Melaka Berhad (SAMB) / Mohd Akmal Musa and Muhammad Syafiq Zabidi - Musa, Mohd Akmal; Zabidi, Muhammad Syafiq (Faculty of Administrative Science and Policy Studies, 2014)
Absenteeism constitutes one of the problems that occur in organization which affect not only the employee’s performance, but also the performance of the organization in term of productivity, production as well as services. The main objective of this research is to determine the factors that influence on absenteeism at Syarikat Air Melaka Berhad (SAMB). Besides that, the researchers also had identified the relationship between the factors that influence absenteeism. Among the factors are workplace environment, individual lifestyle, general stress, and job payment. The researchers has used questionnaire as a main instrument in data collection method. A sample of 148 staffs from the overall of 235 staffs in the company, were taken as the respondents in this study. The statistical techniques used in this study are descriptive statistics, correlation method, and Spearman Rank correlation. This study revealed that the most contributing factor that influence on the absenteeism is workplace environment. Meanwhile, the absenteeism problem is also being influenced by other factors such as general stress, individual lifestyle, and job payment which also obtained a positive relationship. Hence, several recommendations have been provided in order to cope with the problem of absenteeism in the company.